Spectral analysis of geomagnetic data from Kandilli Observatory, Istanbul - Y. K. Tulunay; A. H. Bilge (Annals of Geophysics, 1997)
The geomagnetic field variation spectra for periods longer than 2 h are analysed using the data obtained at the Kandilli Observatory in Istanbul, Turkey. Among the deterministic components, only the harmonics of the solar daily variation (Si) and the second harmonic of the lunar daily variation (L2) were observed. The seasonal dependence of the D component is analysed; the first harmonic of the solar daily variation (S1) has maximum power in summer, decreasing symmetrically towards the winter; the second harmonic (S2) has equal power in spring, summer and fall, while the third harmonic (S3) has maximal power in spring and fall.